Post-Covid-19 Nusa Penida Tourism Recovery as a Sustainable Spiritual Tourism Area - Firlie Lanovia Amir; Komang Shanty Muni Parwati; I Made Darsana (Budapest International Research and Critics University, 2022)
This paper aims to study and formulate a tourism recovery strategy for Nusa Penida after Covid-19 as a sustainable spiritual tourism area, so as to increase tourist visits, extend length of stay and increase people's income without neglecting the preservation of nature and culture in the Nusa Penida Island area. Using a qualitative research approach, to obtain an appropriate strategy, a SWOT analysis is used, which begins with identifying the internal strategic factors and external strategic factors that influence the development of Nusa Penida Island. The results of the analysis show that there are four sets of alternative strategies that can be formulated, namely (1) increasing promotion, (2) structuring and maintaining environmental sustainability, and involving the community in tourism development, (3) developing more varied tourist attractions and developing tourism facilities and public facilities, (4) establish a management body and improve human resources.